A histopathology study on the effects of acute exposure of tropical analgesic spray on brain tissues of sprangue dawley rats - Jessudass N.T.,; Tan, E.L.Y. (Malaysian Society of Applied Biology, 2016)
Topical analgesic sprays are a group of drugs that inhibits the action of pain receptors (nociceptors) resulting in a pain relieving effect. In Malaysia, the abuse of topical analgesic sprays via inhalation is now growing in popularity amongst teenagers as it causes a “high” effect and it is easily available in pharmacies. This study aimed to determine the morphological changes in the brain tissue of Sprague Dawley rats exposed acutely for 14 days to two different brands of topical analgesic sprays. 15 rats were divided into 3 groups; control group, Group A for Medgeneral Ethyl Chloride spray and group B for Perskindol Cool Spray. Each group consisted of 5 rats. The rats were exposed to their specific sprays twice a day for 14 days. On the final day, all rats were sacrificed and the brain tissues underwent gross examination and histological preparations for microscopic viewing. The tissues were examined via comparison microscope and comparisons were made between the control group and the exposed group and also between the two exposed groups. For the brain morphology, both Group A and B showed an increase in pyknotic nuclei, elongated microglia and macrophages compared to control group. Group A showed a higher number of the three morphological findings compared to group B. These results were evident that solvents present in the sprays causes cellular damage and cell death. The results showed that acute exposure of topical analgesic sprays via inhalation causes morphological changes in the brain tissues due to cellular damage and death. However, biochemical tests should be done to determine the mechanism of toxicity caused by the topical analgesic sprays.